Evaluation of Serum NLRC4 as a Potential Prognostic Biochemical Marker in Humans with Severe Traumatic Brain Injury: A Prospective Cohort Study - Tang B; Zhong Z; Wu J; Ma J; Li L; Zhong X; Lin D; Hu J; Yu P (Dove Medical Press, 2023)
Bei Tang, Ze Zhong, Jinping Wu, Jianping Ma, Li Li, Xuzheng Zhong, Dongmei Lin, Jiayuan Hu, Pingan Yu Department of Critical Care Medicine, The First People's Hospital of Jiande City, Jiande, People's Republic of ChinaCorrespondence: Ze Zhong, Department of Critical Care Medicine, The First People's Hospital of Jiande City, Jiande, People's Republic of China, Tel/Fax +86 571 64096607, Email jdsytbzz@126.comObjective: Involvement of NLR CARD domain containing 4 (NLRC4) in neuroinflammation has been demonstrated. The aim of this study was to ascertain the prognostic role of serum NLRC4 in severe traumatic brain injury (sTBI).Methods: In this prospective cohort study including 140 sTBI patients and 140 controls, serum NLRC4 levels were quantified. Follow-up time was 180 days after trauma and poor prognosis was designated as extended Glasgow outcome scale (GOSE) scores of 1- 4. Severity correlations and prognosis associations were determined under multivariate models.Results: Enhanced serum NLRC4 levels after sTBI, in comparison to controls (median, 0.8 ng/mL versus 0.1 ng/mL; P < 0.001), were independently correlated with Glasgow coma scale (GCS) scores (β, − 0.091; 95% confidence interval (CI), − 0.161- 0.021; P = 0.011), Rotterdam computed tomography (CT) scores (β, 0.136; 95% CI, 0.024- 0.248; P = 0.018), serum C-reactive protein levels (β, 0.016; 95% CI, 0.002- 0.030; P = 0.025) and 180-day GOSE scores (β, − 0.906; 95% CI, − 1.632- 0.180; P = 0.015); and were independently predictive of 180-day death (odds ratio, 4.307; 95% CI, 1.706- 10.879; P = 0.014)), overall survival (hazard ratio, 2.360; 95% CI, 1.118- 4.981; P = 0.040) and poor prognosis (odds ratio, 6.705; 95% CI, 2.889- 15.561; P = 0.016). Under receiver operating characteristic curve, combination of serum NLRC4 levels, GCS scores and Rotterdam CT scores had significantly higher death predictive ability than Rotterdam CT scores (P = 0.040), but not than GCS scores (P = 0.070); and exhibited substantially higher predictive capability for poor prognosis than Rotterdam CT scores (P < 0.001) and GCS scores alone (P = 0.023).Conclusion: There is a dramatical elevation of serum NLRC4 levels after sTBI, which has strong correlation with severity and inflammation, and is significantly associated with long-term death and poor outcome, substantializing serum NLRC4 as an inflammatory, prognostic biomarker in sTBI.Keywords: traumatic brain injury, nucleotide-binding domain leucine-rich repeat-containing protein family caspase activation and recruitment domain-containing protein 4, severity, prognosis, biomarkers, inflammation